2005
DOI: 10.18637/jss.v014.i10
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate Poisson and Diagonal Inflated Bivariate Poisson Regression Models inR

Abstract: In this paper we present an R package called bivpois for maximum likelihood estimation of the parameters of bivariate and diagonal inflated bivariate Poisson regression models. An Expectation-Maximization (EM) algorithm is implemented. Inflated models allow for modelling both over-dispersion (or under-dispersion) and negative correlation and thus they are appropriate for a wide range of applications. Extensions of the algorithms for several other models are also discussed. Detailed guidance and implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 26 publications
2
91
0
5
Order By: Relevance
“…(a) Karlis & Ntzoufras [18] considered two regression models to fit the data; i.e., bivariate Poisson The estimates of parameters for first four models are reported in the second column of Table 7. The values of AIC and BIC based on the Total Likelihood Function are summarized in the last two columns of Table 7.…”
Section: Model Comparisonmentioning
confidence: 99%
“…(a) Karlis & Ntzoufras [18] considered two regression models to fit the data; i.e., bivariate Poisson The estimates of parameters for first four models are reported in the second column of Table 7. The values of AIC and BIC based on the Total Likelihood Function are summarized in the last two columns of Table 7.…”
Section: Model Comparisonmentioning
confidence: 99%
“…Bohning et al, 1999) that zero-inflated Poisson models are overdispersed relative to simple Poisson models. In the bivariate (multivariate case) it has been shown that the covariance also increases (see, Wang et al, 2003 andNtzoufras, 2005). Hence, inflated models can introduce improvements in several aspects of the data.…”
Section: Zero-inflated Modelsmentioning
confidence: 99%
“…However, here we follow the zero-inflated bivariate Poisson model proposed by Karlis and Ntzoufras (2005). In fact, they propose an extension of the simple zero-inflated model which inflates the probabilities in the diagonal of the probability table.…”
mentioning
confidence: 99%
“…Here an EM algorithm provided by Karlis and Ntzoufras (2005) and its implementation using R (bivpois package) is used. Standard errors for the parameter estimates are calculated using standard bootstrap methods (boot package in R).…”
mentioning
confidence: 99%